Fahr’s Disease a Rare calcific Neurodegenerative Disorder: A case report - Agrahari, Mahendra Kumar; Shrestha, Joon Kumar; Poudel, Gun Raj; Singh, Ranjita (Journal of Advances in Internal Medicine, 2023)
Fahr’s disease, also known as Fahr’s syndrome is a rare neurodegenerative disorder mentioned by abnormal deposition of calcium in the bilateral basal ganglia and other regions of the brain. We report a case presented to us with detailed description diagnosed as Fahr’s disease, the clinical presentation, diagnostic challenges, and treatment options.